2019
DOI: 10.1002/ajmg.a.61124
|View full text |Cite
|
Sign up to set email alerts
|

The burden of rare diseases

Abstract: The subject of rare disease numbers is rife with misconceptions, not just in websites and other layman's literature, but also in the medical literature. Various websites mention numbers that are not validated by any solid data, while in turn the medical literature cites the aforementioned websites as sources, thus perpetuating a number of myths about rare diseases and their burden. We review the existing literature on rare disease numbers, in an attempt to demystify the subject. Specifically, we summarize data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
248
1
14

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 321 publications
(264 citation statements)
references
References 44 publications
1
248
1
14
Order By: Relevance
“…Our estimate of genetic diseases of 71.9% differs from the 39% derived by Ferreira [37] for two reasons-Ferreira defines 'genetic' diseases as those with a single gene annotating a disease entry (derived from the 'Orphadata: Genes' file); and overestimates the total number of disease as groups and subtypes have been included as well as unique clinical entities. We have used a broader, more practical definition of 'genetic', including not only known single genes but diseases known or suspected to be familial with no underlying gene identified; mitochondrial diseases; and chromosomal rearrangements; as derived from the 'Orphanet classification of genetic disorders' by methods described in our supplemental files; and we have excluded double-counts by considering only the number of unique clinical entities.…”
Section: Discussioncontrasting
confidence: 62%
See 1 more Smart Citation
“…Our estimate of genetic diseases of 71.9% differs from the 39% derived by Ferreira [37] for two reasons-Ferreira defines 'genetic' diseases as those with a single gene annotating a disease entry (derived from the 'Orphadata: Genes' file); and overestimates the total number of disease as groups and subtypes have been included as well as unique clinical entities. We have used a broader, more practical definition of 'genetic', including not only known single genes but diseases known or suspected to be familial with no underlying gene identified; mitochondrial diseases; and chromosomal rearrangements; as derived from the 'Orphanet classification of genetic disorders' by methods described in our supplemental files; and we have excluded double-counts by considering only the number of unique clinical entities.…”
Section: Discussioncontrasting
confidence: 62%
“…Ferreira's [37] use of data from the Orphanet Report Series on Epidemiological data [38] to calculate a cumulative prevalence of 6.2% of the general population by considering 798 RDs has limitations as this file contains only a subset of data from Orphadata. The report series file lacks the structured epidemiological data of Orphadata and thus contains the inclusion of overlapping data by including groups, disorders, and subtypes (e.g., Hemophilia B and mild hemophilia B) that are not independent, which would lead to prevalence overestimates.…”
Section: Discussionmentioning
confidence: 99%
“…Rare diseases affect more than 350 million people globally and collectively represent a particularly significant source of morbidity and mortality [1]. Many have an underlying genetic component as demonstrated by a recent review of > 3800 rare diseases listed by Orphanet, which showed that approximately 80% are either exclusively genetic or have genetic subtypes [2].…”
Section: Introductionmentioning
confidence: 99%
“…Many have an underlying genetic component as demonstrated by a recent review of > 3800 rare diseases listed by Orphanet, which showed that approximately 80% are either exclusively genetic or have genetic subtypes [2]. Patients with rare diseases commonly experience multiyear diagnostic evaluations and receive multiple misdiagnoses during that time [1]. Thus, establishing a precise molecular diagnosis can reduce costs by ending this diagnostic odyssey and, in many cases, aiding in medical management [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Rare diseases are collectively common, affecting an estimated 6.2% of the world's population [1], but each rare disease affects fewer than 4 to 5 in 10 000 individuals in Europe or less than 200 000 individuals in the USA [2]. Patients with rare diseases are often disadvantaged by late diagnosis and off-label prescribing of medicines [3].…”
mentioning
confidence: 99%